Hubungan kadar vitamin D dalam darah dengan kejadian tuberculosis paru - Jon Pangarapan Saragih; Bintang Sinaga; Zainuddin Amir (Majalah Kedokteran Nusantara The Journal Of Medical School, 2013)
Introduction : Vitamin D is known to have an important role in macrophage activation and the subsequent restriction of Mycobacterium tuberculosis growth , and it has been implicated as a risk factor for TB. Vitamin D also induced the expression of cathelicidin, which is involved in the first line of defense in TB patients. An association between 25(OH) vitamin D (25[OH]D) levels and TB has been described in several studies.To compare serum vitamin D level in subjects with and without TB, to find out association of serum vitamin D level with TB and association of serum vitamin D level with extent of lesion in chest x ray.Methods : A cross sectional study was conducted in Adam Malik Hospital Medan, Indonesia from Januari to Juni 2013. New TB cases was diagnosed by the presence of acid-fast bacilli on sputum smears and chest x ray. We excluded TB patients with DM, HIV, malignancy, immunosupresan treatment and immunocompromized patients. Non TB subjects were selected randomly from health care staff, who didn’t have TB from anamnesis and chest X ray. The serum concentrations of 25(OH)D were determined by an CLIA methode. Vitamin D deficiency, vitamin D insufficiency, vitamin D sufficiency, vitamin D optimal defined as serum 25(OH)D concentrations of '3d 10 ng/ml, 10–20 ng/ml, 20-30 ng/ml and >30 ng/ml respectively Results : Thirty one subjects with TB and 31 subjects without TB were enrolled. Mean serum vitamin D level of subjects with and without TB were 25.21 (SD 7.93)ng/ml and 21.50 (SD 9.37)ng/ml, respectively (P = 0.098). Vitamin D deficiency was not found in all subjects. Mean serum vitamin D level in far edvanced and minimal lesion in TB patients [21.61 (SD 5.50) ng/ml versus 29.58 (SD 8.39) ng/ml, P = 0.04], respectively. Regression test was performed to asess the influence of vitamin D in extent of lesion of TB patients (R = 0.000 and P model = 0.897). .Conclusion : There was no significant association between serum vitamin D level and TB. There was a significant difference in vitamin D level between far advance lesion and minimal lesion in TB patients. However statistically extent of lesion was not influenced by serum vitamin D level significantly. Serum vitamin D level of subjects without TB was lower than with TB. It remain to be established other factors that influences serum vitamin D level.Keywords : tuberculosis; vitamin D; extent of lesion